INVOLVING TECHNOLOGY IN THE TEACHING AND LEARNING MATHEMATICS - trisno trisno (EduMa: Mathematics education learning and teaching, 2014)
This study proposes a way to involve technology in the area of teaching mathematics. The technology tool is Geogebra4, which is computer software in the teaching and learning mathematics. This technology emphasizes on the use of multiple representations of mathematical concepts by computer software. The objective is to make students consider the representation of mathematical concepts and help them to enjoy studying mathematics. From that thought, hopefully student understanding will improve and their mathematical achievement will increase. The result of this study is five lesson plans for teaching and learning integral using Geogebra